2015
DOI: 10.1111/dmcn.12930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lumbar epidural bupivacaine with fentanyl or clonidine for postoperative analgesia in children with cerebral palsy after single‐event multilevel surgery

Abstract: AUCArea under the curve SEMLS Single-event multilevel surgery AIM To compare diazepam use, muscle spasm, analgesia, and side effects when clonidine or fentanyl are added to epidural bupivacaine in children with cerebral palsy after multilevel orthopaedic surgery.METHOD Fifty children were prospectively randomized to receive clonidine (n=24, mean age 10y 10mo [SD 2y 11mo]) or fentanyl (n=26, mean age 10y 11mo [SD 2y 10mo]).RESULTS There was no difference in primary outcome measures: median diazepam use (fentany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Child self‐report was employed in four studies . A validated measure was reported in 10 out of 12 studies …”
Section: Resultsmentioning
confidence: 99%
“…Child self‐report was employed in four studies . A validated measure was reported in 10 out of 12 studies …”
Section: Resultsmentioning
confidence: 99%
“…Although adding 0.4 µg/kg/h epidural fentanyl to local anesthetic provided better analgesia in children who underwent femoral osteotomy, this adjuvant increased pruritus, nausea and vomiting, and antiemetic use 25. Similarly, adding 2 µg/mL fentanyl and 2.5 µg/mL clonidine to 0.25% bupivacaine (0.5 mL/kg) provided adequate analgesia in children with cerebral palsy after single-event multilevel surgeries,26 but was associated with a significantly higher incidence of vomiting and oxygen desaturation 26. This discrepancy might be explained by differences in postoperative epidural analgesia regimens.…”
Section: Discussionmentioning
confidence: 99%
“…59,74,75 Chalkiadis et al compared diazepam use, muscle spasm, analgesia, and side effects when clonidine or fentanyl was added to epidural bupivacaine in children with CP after multilevel orthopedic surgery. 8 Clonidine and fentanyl provided adequate analgesia with low rates of muscle spasm, resulting in low diazepam use. 8…”
Section: Alpha-cholinergic Agonistsmentioning
confidence: 99%
“…6 A recent large systematic review including 57 studies, showed that pain prevalence varied widely from 14 to 76% and was higher in females, older age groups, and those classified within Gross Motor Function Classification System (GMFCS) level V. 7 Chalkiadis et al described children with spasticity as the largest group of patients referred to a pediatric multidisciplinary pain clinic in Australia. 8 Several authors have also investigated the relationship between spasticity, muscle strength, muscle length, and functional limitations and concluded a complex entity of direct and indirect interactions that has not yet been unraveled. [9][10][11][12] Wright et al found poor relationships (r < 0.40) between the change scores of spasticity and changes of gross motor abilities after injections with BoNT type A, which may imply that tone reduction as a standalone treatment might not be sufficient to reduce functional limitations.…”
Section: Introductionmentioning
confidence: 99%